European Perspectives of North Macedonia: EU Enlargement Challenges - Runcheva Tasev, Hristina (Trans European Policy Studies Association, 2020)
After a decade of positive recommendations for opening accession negotiations with North Macedonia, the European Union has finally launched them in March this year. During this period, for more than ten years, Macedonian authorities faced the challenge of maintaining a level of interest in the European prospects of the country without receiving many positive signals that the integration will happen in reasonable timeframe.